Muscle power: The interaction of cycle frequency and shortening velocity - Martin, J. C. (Exercise and Sport Sciences Reviews, 2007)
Force-velocity, force-time, and force-length relations of muscle are typically evaluated with reductionist techniques in which force is measured while the variable of interest is manipulated. However, force produced during voluntary movement arises from complex interaction of these contractile characteristics. Nonetheless, neuromuscular performance for cyclical, work-producing movements can be predicted from the interaction of average muscle shortening velocity and movement frequency.